2002
DOI: 10.1063/1.1448298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ru thickness on spin flop in synthetic spin valves

Abstract: Synthetic spin valves with structure of sub/Ta/NiFe/IrMn/AP2/Ru/AP1/Cu/CoFe/Ta were systematically studied by varying the Ru thickness in the artificial antiferromagnetic structure. Spin-valve films were deposited using a Nordiko 9606 PVD system and annealed in a magnetic field of 6 kOe parallel to the easy axis of the free layer. MR(H) and M(H) curves of these spin valves were experimentally measured and quantitatively simulated using Boltzmann transport equation and coherent magnetization rotation model. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Spin flop of the magnetization in the SAF occurs when an external magnetic field is applied parallel to SAF layers. Both theoretical [7] and experimental studies [6] have demonstrated that under a certain applied field the minimization of the total energy of the system occurs when the SAF orients orthogonally to the applied magnetic field. Increasing the external magnetic field further, the flopped spins scissor toward the axis of the magnetic field orienting parallel when a high magnetic field is applied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spin flop of the magnetization in the SAF occurs when an external magnetic field is applied parallel to SAF layers. Both theoretical [7] and experimental studies [6] have demonstrated that under a certain applied field the minimization of the total energy of the system occurs when the SAF orients orthogonally to the applied magnetic field. Increasing the external magnetic field further, the flopped spins scissor toward the axis of the magnetic field orienting parallel when a high magnetic field is applied.…”
Section: Resultsmentioning
confidence: 99%
“…They are different from conventional spin valves, in that the pinned FM layer is replaced by a pinned trilayer structure [synthetic antiferromagnet (SAF)] consisting of two antiferromagnetically coupled FM layers separated by a nonmagnetic layer (usually Ruthenium). This design has the advantage of improved thermal and magnetic performances [6] compared to conventional spin valves. The synthetic spin valve samples studied in this paper were sputtered by Seagate Technology.…”
Section: Methodsmentioning
confidence: 99%
“…4 More recently, the spin flop effect in SAFs was used in order to induce crossed anisotropies in the devices where not only the reference layer is exchange coupled with an AF film, but also the sensing layer. [10][11][12][13] Another approach consists of annealing the samples under the specific field values that ensure the magnetization flop. The anisotropy in the soft layer of a magnetoresistive (MR) sensor is required in order to avoid the Barkhausen noise during the magnetization reversal.…”
Section: Introductionmentioning
confidence: 99%
“…The anisotropy in the soft layer of a magnetoresistive (MR) sensor is required in order to avoid the Barkhausen noise during the magnetization reversal. 11,12 However, when the exchange anisotropy is established by spin flop annealing, a model taking the temperature variation of the anisotropy constants into account should be considered. 9 If the structure is deposited under a magnetic field, the exchange anisotropy can be set directly during the deposition process.…”
Section: Introductionmentioning
confidence: 99%
“…However, the outcoupling efficiency of a conventional OLED is typically less than 30%, which means that most of the light is trapped in the glass substrate [3]. To improve the OLED's outcoupling efficiency, many techniques based on eliminating the waveguiding phenomena between the glass substrate and the air have been studied [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%